Construction and evaluation of ternary solid-liquid phase diagram of pyraclostrobin (form IV) and its intermediate in ethanol and N, N-dimethylformamide. (January 2019) - Du, Cunbin; Dong, Ruimei; Qiao, Bin; Jin, Zhudan; Ye, Tingting; Zhang, Ying; Wang, Mingliang
Highlights: The solid-liquid phase equilibrium for pyraclostrobin and its intermediate in binary and ternary systems was studied. NRTL and Wilson models were used to describing the solubility behavior. Isothermal ternary phase diagrams in ethanol and N, N -dimethylformamide was constructed and evaluated. Abstract: In order to improve the purity of target product and reduce the cost of industrial production, the phase diagrams of pyraclostrobin and its intermediate (pheny N -methoxy- N - (2- (( N ′-pyrazinyl) pyrazolyl-3′-oxymethyl) -phenyl) carbamate) in binary and ternary systems was studied. In each ternary phase diagram, there were three crystallization regions (pure pyraclostrobin intermediate, pure pyraclostrobin, and mixture of pyraclostrobin and its intermediate), two co-saturated curves, and one co-saturated point. The crystallization region of pyraclostrobin intermediate was larger than that of pyraclostrobin in ethanol and N, N -dimethylformamide (DMF) at three temperatures. In order to extend application of the obtained binary and ternary systems, the NRTL model and Wilson model were used to describing the solubility behaviour of pyraclostrobin and its intermediate in binary and ternary systems, the value of root-mean-square deviation ( RMSD ) was no more 9.01 × 10 −3, the value of relative average deviation ( RAD ) was a little large, and no more than 5.84%. The calculated results via two models were all acceptable for the binary and ternary solid-liquid phase equilibrium. Ethanol and DMF in different temperature can be applied to separate the mixture of pyraclostrobin and its intermediate.